The aim of this study is to conduct research into the activity carried out by 118 psychotherapists whose work is based on the theory and practice of Massimo Fagioli and constitute the editorial committee of this journal. In order to make this survey possi - Brandizzi, Martina; Armando, Marco; Dario, Claudia; Fiori Nastro, Paolo (Il sogno della farfalla, 2009)
The principal aims of this study are: to assess the drop-out rate from a university psychotherapy service; to indentify the period at major risk for drop-outs; to delineate a profile of the drop-out patient through the research of a significant correlation between drop-out and social and clinical variables, in order to prevent this adverse event. The sample of this study includes 160 patients, which came to our service for a psychotherapy. The anamnestic and clinical information was collected for each patient. The outcome is classified as drop-out, discharged, and remainers. Each patient is submitted to the multidimensional scale SCL-90R during the first interview. A descriptive analysis of all the data collected was made and the principal links between clinical and socio demographic variables and drop-out, and between SCL-90 R score and dropout were detected. About 42% of the patients were drop-outs, among which 86% by the third session, and only 3% after 6 months of psychotherapy. The variables associated with drop-out are: the young age, the fact of being single, of being unemployed, of being referred by the general practitioner, the absence of previous psychiatric contact, and pathological score in the psychotic scale of SCL-90R. In conclusion: the drop-out percentage is high in psychotherapy; the higher rates of drop-out are in the first three sessions; subjects at high risk are young, at the first contact with psychiatric services, therefore are patients in an outset phase, with better feedback at the treatment. It is very important to recognize these subjects to prevent the drop-out.